Solid-State Molecular Motions in Organic THz Generators - Kim, Jongtaek; Park, Young Choon; Seok, Jin Hong; Jazbinsek, Mojca; Kwon, O. Pil (Advanced Optical Materials, 2021)
Organic nonlinear optical salt crystals are widely used as efficient broadband THz generators. Although solid state molecular motions of organic crystals can greatly influence THz generation characteristics, their origin and effects on THz photonics are not clearly identified. In this work, the origin of solid-state molecular motions of the state-of-the-art nonlinear optical organic salt crystals and their effects on THz generation characteristics are theoretically investigated. A model crystal, HMQ-TMS (2-(4-hydroxy-3-methoxystyryl)-1-methylquinolinium 2,4,6-trimethylbenzenesulfonate) with large macroscopic optical nonlinearity, which is very attractive for intense broadband and narrowband THz wave generation, is chosen. The solid-state molecular vibrations of HMQ-TMS crystals can be classified in three frequency regions: phonon mode region, intramolecular motion region, and their mixing region. For the first time for ionic organic crystalline THz generators, the contributions of cationic chromophores and anionic matchmakers on each of vibrational modes are quantitatively separated. In addition, the influence of solid-state molecular vibrations of HMQ-TMS crystals on the generated THz spectra is investigated. These results provide an essential information for design of new organic nonlinear optical salt crystals for THz generators as well as detectors and for optimization of THz generation performance.
Keywords: Frequency regions; Intramolecular motion; Molecular motions; Non-linear optical; Optical nonlinearity; Organic crystal; State of the art; Vibrational modes; nonlinear optics; organic crystals; THz photonics